2017
DOI: 10.1038/srep41299
|View full text |Cite
|
Sign up to set email alerts
|

Controlled doping by self-assembled dendrimer-like macromolecules

Abstract: Doping via self-assembled macromolecules might offer a solution for developing single atom electronics by precisely placing individual dopants at arbitrary location to meet the requirement for circuit design. Here we synthesize dendrimer-like polyglycerol macromolecules with each carrying one phosphorus atom in the core. The macromolecules are immobilized by the coupling reagent onto silicon surfaces that are pre-modified with a monolayer of undecylenic acid. Nuclear magnetic resonance (NMR) and X-ray photoele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 30 publications
0
29
0
Order By: Relevance
“…The diversity of organic molecules and the flexibility of self-assembly process make MLD an attractive and controllable doping technique. Dopants including phosphorus [20][21][22][23][24][25][26][27][28][29][30], boron [8,20,[31][32][33][34], nitrogen [35], arsenic [27,36] and antimony [37] have been introduced to silicon by MLD using commercial or synthetic reagents.…”
Section: Molecular Monolayer Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…The diversity of organic molecules and the flexibility of self-assembly process make MLD an attractive and controllable doping technique. Dopants including phosphorus [20][21][22][23][24][25][26][27][28][29][30], boron [8,20,[31][32][33][34], nitrogen [35], arsenic [27,36] and antimony [37] have been introduced to silicon by MLD using commercial or synthetic reagents.…”
Section: Molecular Monolayer Dopingmentioning
confidence: 99%
“…The areal dose can be modulated by tuning molecule size, monolayer constitutes, reaction time, reaction temperature, and molecular structure. Several strategies on dose modulation have been investigated [20,21,23,24,28,31,37,38]. In the first MLD report, Ho et al [20].…”
Section: Molecular Monolayer Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the SAMM doping is a mild doping technique that causes no lattice damages. The self-assembly nature of the SAMM doping will form a uniform and conformal coverage of semiconductor surfaces and therefore is compatible with 3D or complex structure doping. …”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition, single dopants may be potentially controlled at large scale by combining "top-down" large-scale nanofabrication and "bottom-up" self-assembly. 14 One of the main concerns for solution-based SAMM doping is organic contamination and dopant deactivation. 15−17 Shimizu et al 16 have demonstrated that carbon and oxygen diffused unintentionally into silicon during the thermal annealing process, and they suggested to sacrifice a top layer of 2−3 nm for industrial application.…”
Section: ■ Introductionmentioning
confidence: 99%